Childhood Behavioural Problems and Adverse Outcomes in Early Adulthood: a Comparison of Brazilian and British Birth Cohorts - Hammerton, Gemma (Journal of developmental and life-course criminology, 2019)
Purpose: Examine associations between childhood behavioural problems with criminal behaviour, emotional disorders, substance use and unemployment in early adulthood in two birth cohorts from a middle- and high-income country. Methods: Data were utilised from large, prospective birth cohorts in Brazil (1993 Pelotas Birth Cohort; N = 3939) and the UK (Avon Longitudinal Study of Parents and Children; ALSPAC; N = 5079). Behavioural problems were reported on by parents at age 11 years (including disobeys, temper, lies, fights, steals). Outcomes (assessed with youth between ages 22 and 24 years) included criminal behaviour, emotional disorders, substance use and NEET (not in education, employment or training). Results: In both cohorts, children with ‘conduct problems’ (those with increased probability of all five behaviours at age 11), were at higher risk of criminal behaviour, emotional disorders and NEET in adulthood compared to those with ‘low problems’. Associations for ‘conduct problems’ were stronger in Pelotas compared to ALSPAC for hazardous alcohol use [Pelotas: risk ratio = 1.39, 95% CI = 1.14–1.70; ALSPAC: risk ratio = 0.76, 95% CI = 0.57–1.02] and illegal drug use [Pelotas: risk ratio = 1.32, 95% CI = 1.16–1.50; ALSPAC: risk ratio = 1.05, 95% CI = 0.91–1.20], whereas associations for criminal behaviour [Pelotas: risk ratio = 1.92, 95% CI = 1.29–2.86; ALSPAC: risk ratio = 2.75, 95% CI = 2.04–3.73] and NEET [Pelotas: risk ratio = 1.38, 95% CI = 1.13–1.70; ALSPAC: risk ratio = 3.04, 95% CI = 1.99–4.65] were stronger in ALSPAC. Conclusions: Childhood conduct problems were associated with criminal behaviour, emotional disorders and unemployment in adulthood in both Brazil and the UK. Additional associations were found for substance use in Brazil.